2021
DOI: 10.1101/2021.06.11.21258765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with COVID-19 susceptibility and severity in patients with multiple sclerosis: A systematic review

Abstract: Background: We conducted this systematic review to identify factors associated with coronavirus disease (COVID-19) susceptibility and outcomes among people with multiple sclerosis (MS). Methods: Available studies from PubMed, Scopus, EMBASE, Web of Science, and gray literature including reference list and conference abstracts were searched from December 1, 2019, through April 12, 2021. We included cross-sectional, case-control, and cohort studies that reported risk factors of contracting COVID-19 or its outcom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Nonetheless, it could be deduced that the data released on the elderly might have had some sort of bias, especially in favor of underreporting. In other words, milder forms of myocarditis in elder patients would have easily been overlooked by their possible underlying cardiac diseases [ 21 , 22 ].…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…Nonetheless, it could be deduced that the data released on the elderly might have had some sort of bias, especially in favor of underreporting. In other words, milder forms of myocarditis in elder patients would have easily been overlooked by their possible underlying cardiac diseases [ 21 , 22 ].…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…The outbreak of Coronavirus Disease-2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to a newly emerging pandemic. This globally spreading virus affects people in different ways, with manifestations ranging from no symptoms to hospitalization and death due to acute respiratory distress syndrome (ARDS) [1,2]. More than one year after the outbreak of COVID-19, the number of reported COVID-19 cases exceeds 150 million, with more than 3.5 million deaths [3].…”
Section: Introductionmentioning
confidence: 99%
“…This raised a question regarding whether people living with MS were at higher risk of COVID-19 and were more likely to develop severe symptoms when infected than the general population. A recent systematic review has suggested a mortality rate of 3.5% among MS patients considering suspected/confirmed COVID-19 cases, which is slightly higher than the rate of 2.2% among the general population [ 2 , 7 ]. This study showed that patients on anti-CD20 agents had highest rates of hospitalization and mortality than those on other DMTs.…”
Section: Introductionmentioning
confidence: 99%